A study of sterile pyuria in dengue fever - N., Prashanth V.; ., Sneha (International Journal of Advances in Medicine, 2019)
Background: Dengue fever is an important tropical disease which is endemic in around 110 countries. It infects 50-100 million people worldwide per year. In India case fatality rate is 1-5% for severe Dengue. Between 2015-2017, 790 deaths have been recorded according to NVBDCP data. Global burden of Dengue has increased at least fourfold over last three decades and now 2.5 billion people at risk of disease. This study aims at determining sterile pyuria as a manifestation in patients presenting with Dengue fever, as patients may present with similar symptoms as that of urinary tract infection, thereby preventing unnecessary use of antibiotics. Methods: It is a Cross sectional observational study conducted on 100 consecutive patients with serologically proven Dengue fever. Patients satisfying inclusion and exclusion criteria underwent relevant investigations and in patients with urine routine showing pyuria, urine culture and sensitivity was done to rule out urinary tract infection and look for sterile pyuria. Results: Among 100 patients of dengue studied, age distribution being 18years to 70years, mean age was 33.27±13.2 years of them 78 were male and 22 were female. 41% patients showed pyuria in urine. 25 % patients were culture positive most common being E. coli and 16% patients had sterile pyuria. Conclusions: Sterile pyuria is not a well-recognized entity in Dengue fever and is often missed. This study shows that sterile pyuria is quite common manifestation in dengue fever which resembles urinary tract infection and therefore does not require any empirical antibiotic treatment.